The case of migrant women from the central American northern triangle: How to prevent exploitation and violence during the crossing - Olmedo, Concepción Anguita (2021)
Violence and inequalities suffered by Central American women force their migration. Once the process has begun, they are exposed to greater violence because they are migrants, poor, indigenous or mestizo, women and, sometimes, minors. The journey is the space in which Central Americans, particularly women, are exposed to violence perpetrated by criminal organizations. Orderly and regular mobility would protect them from the dangers to which they are exposed; to this end, migration governance is needed. This analysis works with intersectionality as a theoretical approach and the methodology used was qualitative, based on interviews and a bibliographic review.